Analysis of status and related factors of genital tract Chlamydia trachomatis infection among 250 female sex workers in rural areas - Zhidong QI; Peizhen ZHAO; Shiying HE; Daocheng ZHENG (Pifu-xingbing zhenliaoxue zazhi, 2022)
Objective To analyze the infection rate of genital tract Chlamydia trachomatis infection in female sex workers in rural areas, and explore related risk factors. Methods Convenient sampling was used to enroll 250 subjects in rural areas of Yunfu city, Guangdong province. A questionnaire survey was used to collect demographic characteristics and sexual behavior characteristics. Blood sample from subjects was used for syphilis and HIV testing, while urine sample was collected for detection of gonorrhea and chlamydia, using real time PCR. Results The infection rate of Chlamydia trachomatis in the genital tract was 22.00% (55/250), while the infection rate of Neisseria gonorrhoeae was 11.60% (29/250). The infection rates of syphilis and HIV were 0.80% (2/250) and 0, respectively. In subjects with chlamydia infection, the co-infection rates of gonococcus and syphilis were 40.0% and 0, respectively. The higher infection rate of Chlamydia trachomatis in the genital tract was associated with lower monthly income (OR=3.052), lower education level (OR=2.611), the non-continuous use of condoms in the last month (OR=3.226), more encounter partners per week (OR=2.109). Conclusions Female sex workers in rural areas have a high rate of Chlamydia trachomatis infection in genital tract. It is recommended to strengthen the detection and health education of genital tract Chlamydia trachomatis infection, and improve the self-prevention and risk control awareness of genital tract infection with Chlamydia trachomatis.